2019
DOI: 10.1002/acp.3522
|View full text |Cite
|
Sign up to set email alerts
|

Reducing suggestibility to additive versus contradictory misinformation in younger and older adults via divided attention and/or explicit error detection

Abstract: Younger and older adults are more suggestible to additive (not originally included) versus contradictory (a change to the original) misleading details. Only suggestibility to contradictory misinformation can be reduced with explicit instructions to detect errors during exposure to misinformation. The present work examines how to reduce suggestibility to additive misinformation and whether attentional resources at exposure similarly influence additive and contradictory misinformation. During the misleading ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Passive statements and passive questions produced more misinformation acceptance than contend-assess questions, confirming a portion of our hypotheses. As hypothesized, people accepted more additive misinformation than contradictory misinformation, replicating existing research (Huff & Umanath, 2018; Moore & Lampinen, 2016; Umanath et al, 2019; cf. Frost, 2000; Nemeth & Belli, 2006).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Passive statements and passive questions produced more misinformation acceptance than contend-assess questions, confirming a portion of our hypotheses. As hypothesized, people accepted more additive misinformation than contradictory misinformation, replicating existing research (Huff & Umanath, 2018; Moore & Lampinen, 2016; Umanath et al, 2019; cf. Frost, 2000; Nemeth & Belli, 2006).…”
Section: Discussionsupporting
confidence: 80%
“…Nemeth & Belli, 2006) and can be explained by the metacognitive memory account. Specifically, researchers have found that retrieval monitoring processes are recruited more to reject contradictory misinformation than additive misinformation with multiple sources of converging evidence (Huff & Umanath, 2018; Moore et al, 2018; Moore & Lampinen, 2016; Umanath et al, 2019). Much of this research has focused on recollection rejection.…”
Section: Discussionmentioning
confidence: 99%